2023
DOI: 10.3390/ma16186277
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk Cellulose-Based Adsorbent to Extract Rare Metals: Preparing and Properties

Askhat Kablanbekov,
Svetlana Yefremova,
Feruza Berdikulova
et al.

Abstract: Adsorption is one of the common stages in the hydrometallurgy of rare metals. Its efficiency is largely determined by the quality of the sorbent used. The purpose of this work was to create an activated sorbent based on rice husk cellulose for the extraction of rhenium from aqueous solutions. Two types of cellulose were obtained by treating rice husk with a 1.5% NaOH solution (alkaline cellulose) and a nitric acid solution in ethyl alcohol (Kürschner and Hoffer cellulose). They were tested by IR, SEM, TA, TPD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The percentage of Re (VII) removal was higher for 60 min (96%) compared with 30 min (84%), and it dropped more significantly (from 84% to 32%) in the 30 min process when the initial concentration of Re (VII) increased [71]. Based on the Giles isotherm classification [75], Kablanbekov et al [71] classified the isotherm of Re (VII) removal for 60 min as the C curve considering that the number of sites on the KHC4-600VA surface for Re (VII) adsorption remained constant at all concentrations up to saturation. The Re (VII) adsorption process onto KHC4-600VA was described the best by the Freundlich equation, while in the case of SCActA, it fit well with the Langmuir isotherm model (Table S16).…”
Section: Adsorption Of Rheniummentioning
confidence: 90%
See 4 more Smart Citations
“…The percentage of Re (VII) removal was higher for 60 min (96%) compared with 30 min (84%), and it dropped more significantly (from 84% to 32%) in the 30 min process when the initial concentration of Re (VII) increased [71]. Based on the Giles isotherm classification [75], Kablanbekov et al [71] classified the isotherm of Re (VII) removal for 60 min as the C curve considering that the number of sites on the KHC4-600VA surface for Re (VII) adsorption remained constant at all concentrations up to saturation. The Re (VII) adsorption process onto KHC4-600VA was described the best by the Freundlich equation, while in the case of SCActA, it fit well with the Langmuir isotherm model (Table S16).…”
Section: Adsorption Of Rheniummentioning
confidence: 90%
“…Moreover, the materials treated with alkali showed the highest sorption properties in comparison to rice husk modified with acids. Although C-O-Si bonds were present in rice husk after alkali treatment, silicon removal was achieved almost completely [71]. It can be suggested that as a result, new active sites form.…”
Section: Adsorption Of Leadmentioning
confidence: 99%
See 3 more Smart Citations